Immunosuppressive gentianellane-type sesterterpenoids from the traditional Uighur medicine Gentianella turkestanorum. (July 2021) - Guo, Kai; Liu, Yan-Chun; Liu, Yan; Zhang, Han; Li, Wen-Yuan; Shi, Qiu-Mei; Li, Xiao-Nian; Zeng, Fang; Li, Sheng-Hong
Abstract: Whole plants of Gentianella turkestanorum are commonly used as a traditional Uighur medicine. A phytochemical investigation led to the isolation of eight undescribed gentianellane-type sesterterpenoids (18- epi -nitidasin, gentianelloids D−F, and 18- epi -gentianelloids C–F), one undescribed 11, 12- seco -gentianellane (18- epi -alborosin), and three known analogs (nitidasin, gentianelloid C and alborosin) among which gentianelloid C was found for the first time from a natural source. The structures of these compounds were elucidated by extensive spectroscopic analyses (including 1D and 2D NMR, HRMS, IR, and specific rotation) and in the case of 18- epi -gentianelloid C by the single-crystal X-ray diffraction analysis. A putative biosynthetic route for these sesterterpenoids was proposed. The immunosuppressive activity of the isolated compounds was also evaluated by their ability to inhibit the proliferation of T cells and T cell cytokine IFN-γ production. Nitidasin suppressed IFN-γ production with an IC50 value of 16.50 μM, while gentianelloid F and alborosin inhibited the proliferation of and IFN-γ production in T cells with IC50 values of 12.40–14.66 μM. Graphical abstract: Nine undescribed gentianellane-type sesterterpenoids along with three known sesterterpenoids were isolated from the whole plants of Gentianella turkestanorum . Several compounds showed immunosuppressive activity. Image 1 Highlights: Twelve gentianellane sesterterpenoids were found in Gentianella turkestanorum. Nine of these gentianelloids were undescribed. Several compounds showed immunosuppressive activity. A plausible biosynthetic pathway for gentianelloids was proposed.